Survey Research: The Effectiveness of Teaching Listening Through Story and Music - Bimbi Izumi Sembiring; Meilan Simanullang; Yola Asmoro; Erikson Saragih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
AbstractListening is one of the most basic skill a person who lives in society need to have. Listening and comprehending words and phrases in their native language is not a problem for most people, but apart from that, every language skill requires some training and habituation before it can be used in even the smallest scale of social interaction. Therefore the authors researched two common media of teaching, is music and story. The research aims to prove that these media is still effective and contained a lot of potential for future development. This research collected data essential for the research through an online survey targeted at 10 teachers or lecturers actively teaching English. The results of the research are divided into qualitative and quantitative data and processed separately. The conclusions are then drawn by combining the culmination of both types of data.